Analysis of biosafety practices of professionals working in the intensive care unit: Cross-sectional study (Research, Society and Development, 2021)
The aim of this study is to investigate the use of biosafety practices by health professionals working in an ICU of a public hospital in Teresina-PI. This is a cross-sectional study, approved by the ethics committee (2,583,723), conducted at a state hospital in Teresina-PI, using questionnaires to ICU health professionals. The data were analyzed using the SPSS 17.0 and BioEstat 5.0 programs, using the Chi-square, Wilcoxon and Kruskal Wallis tests. Values with p